Chemotherapy-induced S100A10 recruits KDM6A to facilitate OCT4-mediated breast cancer stemness - Lu, Haiquan; Xie, Yangyiran; Tran, Linh; Lan, Jie; Yang, Yongkang; Murugan, Naveena L.; Wang, Ru; Wang, Yueyang J.; Semenza, Gregg L. (The Journal of clinical investigation, 2020)
Breast cancer stem cells (BCSCs) play a critical role in cancer recurrence and metastasis. Chemotherapy induces BCSC specification through increased expression of pluripotency factors, but how their expression is regulated is not fully understood. Here, we delineate a pathway controlled by hypoxia-inducible factor 1 (HIF-1) that epigenetically activates pluripotency factor gene transcription in response to chemotherapy. Paclitaxel induces HIF-1-dependent expression of S100A10, which forms a complex with ANXA2 that interacts with histone chaperone SPT6 and histone demethylase KDM6A. S100A10, ANXA2, SPT6, and KDM6A are recruited to OCT4 binding sites and KDM6A erases H3K27me3 chromatin marks, facilitating transcription of genes encoding the pluripotency factors NANOG, SOX2, and KLF4, which along with OCT4 are responsible for BCSC specification. Silencing of S100A10, ANXA2, SPT6, or KDM6A expression blocks chemotherapy-induced enrichment of BCSCs, impairs tumor initiation, and increases time to tumor recurrence after chemotherapy is discontinued. Pharmacological inhibition of KDM6A also impairs chemotherapy-induced BCSC enrichment. These results suggest that targeting HIF-1/S100A10-dependent and KDM6A-mediated epigenetic activation of pluripotency factor gene expression in combination with chemotherapy may block BCSC enrichment and improve clinical outcome.